The teacher's guide to music, media, and copyright law - Frankel, James; Technology Institute for Music Educators (New York : Hal Leonard, 2009)
In this era of unprecedented access to information, teachers have a wealth of readily available resources for lesson planning. But determi ning what you can and can't use legally in the classroom is a difficult task. The Guide helps explain in plain English just how information, images, video, and music can be incorporated into any kind of lesson pl an without running afoul of copyright laws. You'll learn: what resourc es you can use without obtaining permission, how to obtain and license the works you need permission to use; how to check the copyright status of any media item, and; how to apply copyright legality examples to re al classroom situations.
Understanding copyright -- A brief (but interesting) history of copy right law -- Copyright and the Information Age -- Fair use -- Copyright or wrong : permissible, infringement, or fair use? -- Crime and punish ment -- The other side of copyright -- Copyright in the classroom -- A copyright how-to guide -- Copyright resources.
Originally published: New York : Hal Leonard, 2008.
"Published in association with The Technology Institute for Music Ed ucators"--Cover.
Includes bibliographical references (p. 249-254) and index.
Keywords: Copyright -- Audio-visual materials; Fair use (Copyright); Copyright -- Music; Copyright and audio-visual education; Copyright -- Interactive multimedia; Copyright infringement; Music -- Instruction and study